2022
DOI: 10.3390/diagnostics12020357
|View full text |Cite
|
Sign up to set email alerts
|

Practical Approach to the Diagnosis of the Vulvo-Vaginal Stromal Tumors: An Overview

Abstract: Background: The category of the “stromal tumors of the lower female genital tract” encompasses a wide spectrum of lesions with variable heterogeneity, which can be nosologically classified on the basis of their morphologic and immunohistochemical profiles as deep (aggressive) angiomyxoma (DAM), cellular angiofibroma (CAF), angiomyofibroblastoma (AMFB) or myofibroblastoma (MFB). Despite the differential diagnosis between these entities being usually straightforward, their increasingly recognized unusual morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…There is usually a prominent vascular component, characterized by thick-walled vessel [ 34 ]. Neoplastic cells exhibit a poorly defined, scant cytoplasm and round, hyperchromatic nuclei; mitoses are absent or rare [ 35 ]. By immunohistochemistry, neoplastic spindle cells stain positively for vimentin, desmin, and smooth muscle actin (SMA) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is usually a prominent vascular component, characterized by thick-walled vessel [ 34 ]. Neoplastic cells exhibit a poorly defined, scant cytoplasm and round, hyperchromatic nuclei; mitoses are absent or rare [ 35 ]. By immunohistochemistry, neoplastic spindle cells stain positively for vimentin, desmin, and smooth muscle actin (SMA) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neoplastic cells exhibit a poorly defined, scant cytoplasm and round, hyperchromatic nuclei; mitoses are absent or rare [ 35 ]. By immunohistochemistry, neoplastic spindle cells stain positively for vimentin, desmin, and smooth muscle actin (SMA) [ 35 ]. Variable expression of CD34 is detected; S100 and cytokeratin markers are usually negative [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…This recurrence is not invasive and easily cured by a second operation. 15 Only a few malignant cases were reported. A study of 50 cases demonstrated that all patients undergo complete resection of the tumor and are followed up from 3 months to 25 years after surgery, and only one case develops sarcoma 2 years after complete resection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Superficial and Aggressive angiomyxomas should be distinguished from other myxoid and vascular tumors, such as angiomyofibroblastoma, cellular angiofibroma, myxoid liposarcoma, myxofibrosarcoma, myxoid desmoid fibromatosis, and myxoid dermatofibrosarcoma protuberans (DFSP), among others. Although these tumors entities may present similarly, they can be diagnosed based on characteristic clinicopathologic, immunohistochemical, and molecular findings ( Angelico et al, 2022 , Baheti et al, 2015 , Ganeshan et al, 2019 , Mentzel et al, 2007 ). Similarly to Aggressive angiomyxoma, angiomyofibroblastoma and cellular angiofibroma also have a predilection to the lower female genital tract.…”
Section: Discussionmentioning
confidence: 99%